Different germination success may explain lower species richness of herbaceous vegetation below non-native than native shrubs - Vojtech Lanta; Kai Norrdahl (Finnish Zoological and Botanical Publishing Board, 2022)
Mechanisms by which invasive species affect native communities have been intensively studied. Invasive plants may influence other species through competition, altered ecosystem processes, or other pathways. It has been suggested that allelochemical interference is the key mechanism explaining a lower species richness of herbaceous plants below non-native than native shrubs. We studied plant recruitment from seeds sown inside and outside patches formed by Sorbaria sorbifolia, a shrub non-native to Finland, and a native shrub Rubus idaeus. Recruitment of seedlings was lower below non-native than native shrubs, in contrast to recruitment outside the shrub patches. Biotic filtering of subdominant plants was a stepwise process affected by the difference between non-native and native shrubs. Our results suggest that allelochemicals released by non-native species may be responsible for this difference. They thus give support to the hypothesis emphasizing the importance of allelopathy in the invasion of non-native plants. The slow and stepwise action of biotic filtering cautions against defining plant community membership merely based on the presence of seedlings.